Safety of combination pharmacotherapy in elderly patients - E. V. Shikh; A. D. Ismagilov; Zh. M. Sizova; O. A. Demidova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article reviews literature data on adverse reactions to drugs. The frequency of suspected adverse reactions in indoor patients over 60 years old is 2-3 times higher than that in patients younger than 30 years. This is due to peculiarities of drugs pharmacokinetics (absorption, distribution, metabolism and excretion) in elderly patients. It might be dangerous to combine medicines that cause the QT interval prolongation. A literature review was performed in order to analyse clinically relevant interactions of drugs that are metabolized by CYP3А4 and are associated with a potential or conditional risk of torsade de pointes. It was shown that in order to increase the safety of pharmacotherapy in elderly patients, it is not recommended to prescribe two drugs at a time that cause the QT interval prolongation, nor is it recommended to prescribe combinations of drugs that could potentially lead to the QT interval prolongation due to a change in metabolism of one of the drugs.